(‐)‐Epigallocatechin gallate‐loaded polycaprolactone scaffolds fabricated using a 3D integrated moulding method alleviate immune stress and induce neurogenesis. (20th November 2019) - Qian, Yun; Yao, Zhixiao; Wang, Xu; Cheng, Yuan; Fang, Zhiwei; Yuan, Wei‐En; Fan, Cunyi; Ouyang, Yuanming
Abstract: Objectives: In peripheral neuropathy, the underlying mechanisms of nerve and muscle degeneration include chronic inflammation and oxidative stress in fibrotic tissues. (‐)‐Epigallocatechin gallate (EGCG) is a major, active component in green tea and may scavenge free radical oxygen and attenuate inflammation. Conservative treatments such as steroid injection only deal with early, asymptomatic, peripheral neuropathy. In contrast, neurolysis and nerve conduit implantation work effectively for treating advanced stages. Materials and methods: An EGCG‐loaded polycaprolactone (PCL) porous scaffold was fabricated using an integrated moulding method. We evaluated proliferative, oxidative and inflammatory activity of rat Schwann cells (RSCs) and rat skeletal muscle cells (RSMCs) cultured on different scaffolds in vitro. In a rat radiation injury model, we assessed the morphological, electrophysiological and functional performance of regenerated sciatic nerves and gastrocnemius muscles, as well as oxidative stress and inflammation state. Results: RSCs and RSMCs exhibited higher proliferative, anti‐oxidant and anti‐inflammatory states in an EGCG/PCL scaffold. In vivo studies showed improved nerve and muscle recovery in the EGCG/PCL group, with increased nerve myelination and muscle fibre proliferation and reduced macrophage infiltration, lipid peroxidation, inflammation and oxidative stress indicators. Conclusions: The EGCG‐modified PCL porous nerve scaffold alleviates cellular oxidative stress and repairs peripheral nerve and muscle structure in rats. It attenuates oxidative stress and inflammation in vivo and may provide further insights into peripheral nerve repair in the future.